2019
DOI: 10.31389/jltc.20
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Relatives of People with Acquired Brain Injury (ABI) of the Condition and Associated Social and Health Care Services

Abstract: IntroductionAcquired Brain Injury (ABI) is a significant issue for longterm care. Data collected in the UK suggest that, on average, 445 people are admitted to hospital with a head injury every day (Headway, 2015b). Many of these injuries caused in, for example, road traffic accidents, assaults, falls and sporting injuries are generally minor, but a significant proportion can cause traumatic damage to the brain. The vast majority (95%) of admissions to hospital with head injury present with a normal or relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Practitioners in the present study consistently reported concerns about other professionals' assumptions of capacity in individuals with ABI. Like Moore et al (2019), practitioners in the present study felt other professionals did not always understand the complexity of brain injury and its presentations, a point made by family members about staff generally (Holloway and Tasker, 2019). This reflects other evidence that many individuals with an ABI can mask their executive functioning difficulties owing to their intact intellect (Acquired Brain Injury and Mental Capacity Act Interest Group, 2014) and intact language abilities (McCrea and Sharma, 2008).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Practitioners in the present study consistently reported concerns about other professionals' assumptions of capacity in individuals with ABI. Like Moore et al (2019), practitioners in the present study felt other professionals did not always understand the complexity of brain injury and its presentations, a point made by family members about staff generally (Holloway and Tasker, 2019). This reflects other evidence that many individuals with an ABI can mask their executive functioning difficulties owing to their intact intellect (Acquired Brain Injury and Mental Capacity Act Interest Group, 2014) and intact language abilities (McCrea and Sharma, 2008).…”
Section: Discussionmentioning
confidence: 53%
“…Different mediating factors seemed to account for the variability in practice. These reflected some of the wider contextual challenges of ABI practice which others have noted is so important (Holloway and Tasker, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…associated with cognitive impairments, particularly the executive impairments that may compromise development of insight (Holloway and Tasker, 2019;Moore et al, 2019;Norman 2016). ABI has long been recognised as a family condition by both social worker authors (Romano, 1974) and others (Lezak, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Since Tom's death in 2014, and even since the publication and release of his SAR in 2017, there have been many publications pertinent to the issue discussed here; the needs of individuals and families affected by ABI that are in the purview or duty of a UK social worker. Academic social work however has proved to have very limited interest in the condition with few articles (albeit an increasing number) published across the English speaking world (Mantell et al, 2012, Mantell et al, 2017Mantell et al, 2018) Work published in recent years, often from outside of the profession, has identified difficulties with an absence of social worker knowledge of ABI and the impact that this has upon other sectors of health and social care, upon family and upon affected individuals (Fins 2015;Holloway, 2014, Golightley & Holloway, 2016Fyson, 2016, Simpson &Yuen, 2018;Holloway and Tasker, 2019, Moore et al, 2019. A review by the House of Lords into how the Mental Capacity Act was working in practice identified significant and specific difficulties relating to ABI (House of Lords, 2014).…”
Section: Publications Since 2014mentioning
confidence: 99%
See 1 more Smart Citation